Characteristics and Causal Mechanism of Topsoil Slip in Ductile Shear Zone of the Shanwei Section of the Lianhuashan Fault Zone - Wang Ping; Wang Xianneng; Lai Anfeng (Redai dili, 2023)
The Shanwei Special Cooperation Zone (SSCZ) in Shenzhen is the main distribution area of the Lianhuashan Fault Zone. Two large ductile shear zones pass through the SSCZ. The ductile shear zone of the SSCZ is henceforth referred to as "the zone". Severe plastic progressive deformation, stretching, and compression occurred in the late Jurassic-Neogene period in the zone, because of which the structure and properties of the rock mass underwent significant changes. There are three levels of structural planes in the zone: brittle faults, schistosity planes, and joints in the rock mass. The ductile shearing action changes the rock mass structure, leading to poor integrity. According to existing data, the compressive strength of the rock in the zone is equivalent to 0.31-0.86 of the original rock, indicating that the strength of the rock is obviously attenuated by ductile shear action. Using ground investigation and remote sensing, we found 1,614 topsoil slips in the zone. The density of topsoil slips in the hillside area (16.2 topsoil slips per km2) was much higher than that outside the zone (1.3 topsoil slips per km2), indicating that the slopes in the zone are more prone to shallow damage. To study the geological risk zonation of geological hazards in the SSCZ, it is necessary to determine the characteristics and distribution rules of topsoil slips in the zone, analyze its causal mechanism, and predict its development trend.ⅰ) Ground surveys and remote sensing showed that monocase topsoil slip is small in the zone and sliding mainly occurs along the bedrock surface. Sliding masses are mainly solid and completely weathered rock. ⅱ) The frequency of geological disasters under the action of certain factors in the study area is divided by the frequency of geological disasters in the area. The natural logarithm of the divisor is taken as the information value to evaluate the relationship between geological disasters and various factors. The results show that the density of topsoil slips is positively correlated with the degree of ductile deformation (strong→medium→weak), distance from brittle fracture (near→far), and topographic slope (high→low). Moreover, the distribution density is strongly related to the geomorphic unit, slope direction, original rock type, and slope type. ⅲ) The above analyses are combined with regional, geological, exploration, meteorological, and other data. Results from this combination show that topsoil slips in the zone are produced under weak background conditions formed by the influence of multi-stage tectonic action dominated by ductile shear forces, the slow rise of the hillside area, and the induction of typhoons and rainstorms. Their development and changes are characterized by migration, self-healing, and expansion. ⅳ) Most of the current topsoil slips occurred during Super Typhoon Mujigae in 2015, after which the region experienced several rainfall events with intensities higher than those of Typhoon Mujigae, yet the number of topsoil slips did not increase significantly. This shows that after a general shallow sliding event, the sensitivity of the slope to shallow damage decreased, and generation took a long time before entering the next outbreak period.